Spiritual Accountability Practices in Discipleship among the Indonesian Seventh-day Adventist Members in Manila, the Philippines - Simbolon, Mangadar; Zebedeus, Davied Yosua Abraham (8ISC Abstract Proceedings, 2022)
Being the disciples of God creates a need for agreeing to hold each other accountable in a manner pleasing to the Lord. Accountability would be a recommended experience when friends hold each other accountable for such spiritual progress. However, the practices might be unknown to the pastor or the Seventh-day Adventist church members if there is no clear intention. Most of the time, they would not remember spiritual accountability. Accountability can be a means for Christian discipleship to get closer to Jesus through the fellowship of others. This research study aims to delve into the practices of spiritual accountability among church members. Spiritual accountability will be generally defined as strengthening one another in their vulnerability to progress spiritual growth. The level of spiritual maturity of this young church with young people as the members is unable, yet in progress, to actively practice spiritual accountability in such intensive or proper ways. The socio-cultural barriers, alongside the spiritual hesitance, somehow hinder the daily accountability practices among church members. Nevertheless, the teaching of accountability with spiritual emphasis and the suggested programs will enhance its understanding and practice among the church members. This research study utilizes the qualitative research method through in-depth and focused group interviews and literature reviews as data sources. The participants are particularly from an Indonesian Seventh-day Adventist (SDA) Fellowship in Pasay City, Manila. Keywords : Discipleship, spiritual accountability, Seventh-day Adventist, church